2017
DOI: 10.1021/acsami.7b02975
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Interface Characteristics of Neural Probe Based on Graphene, ZnO Nanowires, and Conducting Polymer PEDOT

Abstract: In the growing field of brain-machine interface (BMI), the interface between electrodes and neural tissues plays an important role in the recording and stimulation of neural signals. To minimize tissue damage while retaining high sensitivity, a flexible and a smaller electrode with low impedance is required. However, it is a major challenge to reduce electrode size while retaining the conductive characteristics of the electrode. In addition, the mechanical mismatch between stiff electrodes and soft tissues cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 51 publications
1
50
1
Order By: Relevance
“…Ryu et al of the Daegu Gyeongbuk Institute of Science and Technology demonstrated a neural probe structure based on graphene, ZnO nanowires, and conducting polymer that provides flexibility and low impedance performance [ 87 ]. As shown in Figure 6 f, the hybrid Au and graphene structure was utilized to achieve both flexibility and good conductivity.…”
Section: Research Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryu et al of the Daegu Gyeongbuk Institute of Science and Technology demonstrated a neural probe structure based on graphene, ZnO nanowires, and conducting polymer that provides flexibility and low impedance performance [ 87 ]. As shown in Figure 6 f, the hybrid Au and graphene structure was utilized to achieve both flexibility and good conductivity.…”
Section: Research Progressmentioning
confidence: 99%
“… Research progress of the electrode-tissue interface modification technology of flexible MEMS microelectrodes for neural interface. ( a ) PEDOT/PSS composite film, reprinted from [ 3 ] with permission of Elsevier, Copyright 2002; ( b ) PEDOT/biomolecules composite film, reprinted from [ 83 ] with permission of Springer, Copyright 2008; ( c ) PEDOT/carbon nanotube (CNT) composite film, reprinted from [ 80 ] with permission of Elsevier, Copyright 2011; ( d ) PEDOT composite nanotubes, reprinted from [ 73 ] with permission of John Wiley and Sons, Copyright 2009; ( e ) PEDOT/graphene oxide (GO) composite film, reprinted from [ 84 ] with permission of Elsevier, Copyright 2013; ( f ) PEDOT-Au-ZnO nanowires, reprinted from [ 87 ] with American Chemistry Society, Copyright 2017. …”
Section: Figurementioning
confidence: 99%
“…[5] In this line, a series of flexible electrodes have been proposed, [18][19][20] but only a few combine flexibility with nanostructure. [21,22,23] For instance, Rogers and colleagues described a bio-interfaced system based on ultrathin electronics supported by bioresorbable substrates of silk fibroin, [18] which assures minimal stresses on the tissue and highly conformal coverage. Authors proved the utility of these interfaces to record neural activity in the feline visual cortex.…”
Section: Introductionmentioning
confidence: 99%
“…[22] On the basis of hydrothermally grown ZnO NWs over a metalized polyimide layer, Ryu et al described stable flexible neural probes with low impedance after a two steps coating process with gold and PEDOT. [23] So, in order to achieve flexibility, either non-metallic solutions are used, at the cost of an increase in impedance, or a many-step growth process is required to finally metalize the sample.…”
Section: Introductionmentioning
confidence: 99%
“…flexible organic bioelectronics. [13][14][15][16] Recently, graphene and carbon nanotube (CNT) based electrodes gained considerable interest for neural and cardiac interfacing, [17][18][19][20][21] as well as implant coatings [22,23] and stem cell therapy. [24][25][26] Their high surface-to-volume ratio and enhanced electron transfer [27] dramatically lower electrode impedance, resulting in improved cell recording and stimulation.…”
Section: Introductionmentioning
confidence: 99%